La guerre du Chaco et ses survivants dans la littérature paraguayenne - Carla Fernandes (Amnis)
It is usually considered that the war of Chaco generated few literary productions. However, since 1934 until today, some literary works – based on this event – are published. Their analysis shows that at the beginning, the representation of this war and of its victims follows a model concerned with credibility, which is that of the various testimonies written after the conflict. As new texts appear, the representation gives up this mimetic report, to be based on already existing texts according to a hypertextual logic, and they develop, at the same time, a more symbolic and universal approach of the war and its victims. The most recent productions reveal new modalities, such as fantastic or humor, which question the very existence of theevents.